Orofacial muscles may be affected in early stages of Becker muscular dystrophy: A preliminary study. Issue 2 (24th December 2019) - Lagarde, Marloes L.J.; van Alfen, Nens; Geurts, Alexander C.H.; de Groot, Imelda J.M.; van den Engel‐Hoek, Lenie
Abstract: Background: Dysphagia is reported in patients with Duchenne or Becker muscular dystrophy. Our clinical experience suggests that, compared with Duchenne patients, impaired mastication and swallowing occur early in Becker patients relative to their skeletal muscle involvement. The aim of this study was to assess dysphagia in Duchenne and Becker patients in relation to ambulatory capacity. Methods: In patients in the early ambulatory stage, clinical symptoms, quantitative muscle ultrasound of the orofacial muscles, and maximum bite force were assessed. The 6‐Minute Walk Test (6MWT) was used to measure ambulatory capacity. Results: Eleven Duchenne and 11 Becker patients were included. Although Becker patients had a greater 6MWT distance than Duchenne patients, the occurrence of mastication and swallowing difficulties was similar. The temporalis muscle was significantly thicker in Becker patients. Conclusions: Clinicians should be aware of dysphagia in both groups, even when ambulation is still well preserved.